Measured impacts of supply vs. exhaust ventilation in residences - Paul W. Francisco; Kiel Gilleade; Yigang Sun; Zachary Merrin; Masih Alavy; Jason LaFleur (Indoor Environments)
It is well-recognized that ventilation in residential buildings is important for maintaining acceptable indoor air quality. Many residential energy retrofit programs require the installation of ventilation when energy-saving measures such as air sealing are performed on homes. However, there is substantial disagreement about the relative merits of supply ventilation, which brings outdoor air directly into the home, vs. exhaust ventilation, which targets the direct removal of contaminants from the home to outdoors. Past studies to explore this issue have used modeling, testing of unoccupied homes using tracer gases, and comparisons between homes that had different ventilation strategies. This study measured multiple contaminants in 18 lived-in homes in which both supply and exhaust ventilation systems were installed, at similar ventilation rates. Measurements were made over three weeks: one week with no ventilation operating, one week with exhaust ventilation operating, and one week with supply ventilation operating. Because both ventilation strategies were tested in the same homes, the analysis avoids a number of confounding factors based on any differences in homes. The results show that both ventilation strategies reduce contaminants by a similar amount, with differences in contaminant levels between system types not statistically significant. Most reductions were on the order of 10 %, with particles being reduced by 25–30 %. Apparent differences between the strategies differ depending on the contaminant, with exhaust having slightly larger reductions in contaminant levels for most contaminants, but supply having a greater beneficial impact on basement-level radon. The results suggest that there is a similar reduction of contaminant levels regardless of how ventilation is provided to the home.